The influence of inflammation on the characteristics of adipose-derived mesenchymal stem cells (ADMSCs) and tissue repair capability in a hepatic injury mouse model - Jingfang Xiao; Xiaoyuan Gong; Zhenlan Fu; Xiongbo Song; Qinghua Ma; Jingya Miao; Ruili Cai; Zexuan Yan; Shuai Wang; Qian Li; Yaokai Chen; Liu Yang; et al. (Stem Cell Research & Therapy, 2023)
Abstract Background Mesenchymal stem cells (MSCs) are adult stem cells with self-renewal and multi-directional differentiation potential and possess the functions of immunomodulation, regulation of cell growth, and repair of damage. Over recent years, MSCs have been found to regulate the secretion of inflammatory factors and to exert regulatory effects on various lymphocytes in inflammatory states, and on the subsequent repair of tissue damage caused by inflammation. In the present study, we analyzed the effects of tissue inflammation on the characteristics of MSCs. Methods Human fat derived from the infrapatellar fat pad (IPFP) of knees with differing degrees of inflammation was extracted from specimens derived from total knee arthroplasties. HE and immunohistochemical staining was performed to directly observe the evidence and degree of inflammation in human infrapatellar fat pad tissue in order to classify MSCs cells, by their origin, into highly inflamed and lowly inflamed groups, and to study the effect of tissue inflammation on cell acquisition rates via cellular counting data. Flow cytometry assays were performed to investigate the effect of tissue inflammation on MSC surface marker expression. Trilineage differentiation, including osteogenesis, adipogenesis, and chondrogenesis, was performed to assess the effect of tissue inflammation on the ability of MSCs to undergo directed differentiation. The effect of tissue inflammation on the ability of MSCs to proliferate was investigated via clone formation studies. RNA-sequencing was performed to evaluate the transcriptomes of MSCs derived from different areas of inflammation. The effect of tissue inflammation on tissue repair capacity and safety of MSCs was investigated via a murine model of acute liver injury. Results The results of cell count data indicate that a high degree of tissue inflammation significantly decreases the acquisition rate of MSCs, and the proportion of CD34+ and CD146+ cells. The results of our trilineage differentiation assay show that a higher degree of inflammation decreases osteogenic differentiation and enhances adipogenic and chondrogenic differentiation of MSCs. However, these differences were not statistically significant. Clone formation assays indicate that the degree of tissue inflammation at the MSC source does not significantly affect the proliferative capacity of MSCs. The transcriptomes of MSCs remain relatively stable in fat pad tissues derived from both highly and lowly inflamed samples. The results of acute liver injury investigations in mice indicate that MSCs of high and low inflammatory tissue origin have no significant difference in their tissue repair capability. Conclusions High tissue inflammation at the source of MSCs reduces the acquisition rate of MSCs and the percentage of CD34+ and CD146+ cells acquisition. However, source tissue inflammation may not significantly affect trilineage differentiation potential and proliferative capacity of MSCs. Also, MSCs obtained from differing source degrees of inflammation retain stable and similar transcriptomic profile and are both safe and efficacious for tissue repair/regeneration without detectable differences. Graphical Abstract